2022
DOI: 10.1055/a-1797-9587
|View full text |Cite
|
Sign up to set email alerts
|

Role of gastric per-oral endoscopic myotomy (G-POEM) in post-lung transplant patients: a multicenter experience

Abstract: Background and study aims Gastroparesis post-lung transplant (LTx) can lead to increased risk of gastroesophageal reflux (GER) and accelerated graft dysfunction. We aimed to evaluate the efficacy and safety of gastric per-oral endoscopic myotomy (G-POEM), a promising tool in patients with refractory gastroparesis, for managing refractory gastroparesis and GER in post-LTx patients. Patents and methods This was a multicenter retrospective study on post-LTx patients who underwent G-POEM for management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…There no other reports of G-POEM in post PT population in the literature, making it difficult to assess the incidence of adverse events related to the procedure, but the rate of 14% (one in seven) in our cohort does seem to compare to the rate in the post lung transplant population according to a retrospective multicenter trial. 50 We anticipate that the rate of complications will decrease as both our population and experience level continues to increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There no other reports of G-POEM in post PT population in the literature, making it difficult to assess the incidence of adverse events related to the procedure, but the rate of 14% (one in seven) in our cohort does seem to compare to the rate in the post lung transplant population according to a retrospective multicenter trial. 50 We anticipate that the rate of complications will decrease as both our population and experience level continues to increase.…”
Section: Discussionmentioning
confidence: 99%
“…The first G-POEM in the post pancreatic transplant population was also performed in 2018 (Figure 1). In the literature, the use of G-POEM in the post-transplant population is most prevalent in lung transplant recipients 49,50 with no reported studies in patients status post pancreas transplant. In our single institution study, all patients were found to have some benefit after G-POEM.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Some small studies have shown that G-POEM in gastroparesis improves pH testing. 20 Ishak et al, evaluated 6 patients with gastroparesis and refractory reflux that underwent Dor fundoplication, pyloroplasty, and GES, who all showed significant improvement in heartburn and regurgitation scores after the procedure. 16…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Some small studies have shown that G-POEM in gastroparesis improves pH testing. 20 Ishak et al, evaluated 6 patients with gastroparesis and refractory reflux that underwent Dor fundoplication, pyloroplasty, and GES, who all showed significant improvement in heartburn and regurgitation scores after the procedure. 16 Our patients experienced significant improvement in both classic gastroparesis symptoms as well as heartburn and reflux symptoms after the placement of temporary and subsequent permanent gastric stimulators.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter retrospective study of 20 lung transplant patients with concomitant GERD and gastroparesis demonstrated normalization of pH testing in 90% with improvement in gastric emptying and ability to wean off PPI therapy in 75%. 131 …”
Section: Invasive Anti-reflux Managementmentioning
confidence: 99%